Evaluation of edible oil types used in packaged foods in Turkiye with principal component analysis - Icyer, Necattin Cihat; Kuran, Nesrin (Wiley, 2024)
In our rapidly changing world, where consumers' expectations for healthy food are on the rise, the edible oil content in packaged foods has become a central focus. Among various types of oils, palm oil is often regarded as one of the most contentious. This research study aimed to identify the types of fats present in packaged food products in Turkiye and examined the reasons for their utilization. A total of 1380 packaged food items, classified into 11 categories, were scrutinized, and the types of oils within their ingredients were classified using principal component analysis and hierarchical cluster analysis. The study's results have determined that among packaged food products available in Turkiye, 50.1% contain palm oil, 30.4% contain sunflower oil, 16.4% contain canola oil, 14.9% contain cottonseed oil, 17.9% contain cocoa oil, and 12.6% contain coconut oil. In particular, it was determined that palm oil was used in 91% of bakery products, 81% of margarine and shortening products, and 71.3% of ice creams. Consequently, the data obtained in the context of ongoing debates regarding the fat content in packaged foods, especially concerning palm oil usage, will make a valuable contribution to the literature.
Keywords: edible oils; food labeling; hierarchical cluster analysis; palm oil; principal component analysis